Decorative Effect in the Solution of Children’s Drawings on Historical Topics. - AKISHINA, Ekaterina; SEVRYUKOVA, Nadezhda (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article analyzes decorative drawings sent to the All-Russian Drawing Competition among students of general education organizations for the 500th anniversary of the Tula Kremlin (Tula, Russia) on the topic "Tula Kremlin is the pride of Russia". The relevance of studying the decorative solution of children’s drawings is associated with the fact that decorative drawing most fully reflects the child’s desire to express their emotional attitude to reality. The article analyzes the decorative effect of children’s drawings on historical themes; classifies competitive drawings; considers artistic techniques that help to direct the creative search of a student on the path of emotional artistic development. RESUMEN El artículo analiza dibujos decorativos enviados al Concurso de Dibujo de toda Rusia entre estudiantes de organizaciones de educación general por el 500 aniversario del Tula Kremlin (Tula, Rusia) sobre el tema "Tula Kremlin es el orgullo de Rusia". La relevancia de estudiar la solución decorativa de los dibujos infantiles está asociada con el hecho de que el dibujo decorativo refleja más plenamente el deseo del niño de expresar su actitud emocional ante la realidad. El artículo analiza el efecto decorativo de los dibujos infantiles en temas históricos; clasifica dibujos competitivos; considera técnicas artísticas que ayudan a dirigir la búsqueda creativa de un estudiante en el camino del desarrollo artístico emocional.